Seed yield and physiological quality of soybean in different environments - Gomes, Greice Daiane Rodrigues; Benin, Giovani; Rosinha, Rui Colvara; Galvan, Danielle; Pagliosa, Eduardo Stefani; Pinnow, Cilas; Silva, Cristiano Lemes da; Beche, Eduardo (Semina: Ciências Agrárias, 2012)
The objective of this study was to evaluate the physiological quality and seed yield of soybean cultivars produced in Campo Mourão and Guarapuava, Paraná State, and Guaíra in the São Paulo State. Seeds of nine cultivars from trials network of the Fundação Pró-Sementes were used for analysis. The experimental design was in randomized blocks in factorial scheme 3 x 9 (cultivars x environments), with three replications. The evaluation of seed quality was performed using the germination and vigor tests, and through the accelerated aging and Tetrazolium tests. The results showed that the physiological quality and seed yield were influenced by the sowing environment. Soybeans seeds from the region of Guarapuava-PR had higher germination, vigour and viability, compared the regions of Campo Mourão-PR and Guaíra-SP. The mechanical and moisture damage were mainly causes for the decrease in germination, vigor and viability of seeds at all regions evaluated. The cultivars CD 214 RR, BRS 246 and BRS 255 RR showed high yield and seed quality.